In depth Analysis of Brand Alliance Strategy: A Case Study of Luckin Coffee and Moutai - Zhang Jiaming (SHS Web of Conferences)
In today’s increasingly competitive market climate, brand alliance strategy has emerged as one of the most essential approaches for businesses to acquire market advantage through resource integration. The joint example of Luckin Coffee and Kweichow Moutai, a milestone cross-category collaboration, provides substantial practical insight into the brand’s joint approach. This paper investigates the rationale, implementation process, successes, and problems of brand alliances using the case study of Luckin Coffee and Kweichow Moutai. The example demonstrates how Luckin was able to increase the value of its brand by using Moutai’s high-end brand image and long-standing cultural legacy. At the same time, Moutai has used this chance to broaden its customer base and market reach. However, the two parties’ brand alliance introduces dangers such as mismatched brand representations, contradictory strategic aims, and customer acceptance. The study also offered risk identification, assessment, and response tactics, with the goal of serving as a reference and advice for similar brand joint programs.